Comparison of loss on ignition method and hydrogen peroxide method in determining the percentage of organic matter in soils - Nor Shalihah, Hasbullah (2019)
The soil erodibility factor (K factor) of the USLE equation represents an indicator of the susceptibility of a soil to raindrop impact, runoff and other erosion processes. It can be affected by many factors such as soil type, infiltration rate, permeability rate, and organic matter content. The purpose of this study is to provide a comparison in determining the percentage of organic matter content in soil. Soils sample for this study were collected randomly. The samples were analyzed for organic matter content using two different methods whish are loss on ignition (LOI) method and hydrogen peroxide digestion (H2O2) method. For LOI method, it more directs method where the sample is ignited. For H2O2 method it is more complicated because it uses heated H2O2 to decompose the organic matter inside the soil. From the results obtained, the LOI method provided the highest but comparably similar percentage of organic matter content with the H2O2 method. The total organic matter in soils by H2O2 method shows slightly lowers value to the LOI method. In addition, the H2O2 method mostly gives low results for several soils sample. But by using H2O2 method it gives the smaller errors in during calculation of percentage of organic matter content. LOI sometimes gives too high or very low results, and occasional large the error. This because the percentage of organic matter is only calculated the loss of weight after combustion. Conclusion is the best method of determine the percentage of organic matter content is by using the LOI method, but the temperature use for combustion need to be consider based on the type of soils to make sure that it totally complete the combustion stage of soils.